PENGARUH SALES GROWTH DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2018 (Universitas Gajayana Malang, 2019)
This research aims to determine the influence of sales growth and size of the company against the dividend policy in manufacturing companies of food and beverage subsectors listed on the Indonesia Stock Exchange period 2013-2018. Research is conducted using quantitative methods. The data used in this research is derived from the financial report data taken from the official website of the Indonesia Stock Exchange. The population of this research is a manufacturing company of food and beverage subsectors listed on the Indonesia Stock Exchange period 2013-2018. Sampling techniques with purposive sampling there are 7 companies within 6 years 2013-2018 that correspond to the criteria. The data analysis methods of this research are descriptive statistical analyses, classical assumption tests, multiple correlation analyses, multiple linear regression analyses, coefficient of determination, and its data processing using SPSS 21.0 for Windows. The results of a partial analysis can be concluded that the sales growth has significant effect on the dividend policy. The company's size has significant effect on dividend policy. And simultaneously it can be concluded that the sales growth and size of the company significantly affects the dividend policy. Keywords: Company size, Dividend policy, Sales Growth